2016
DOI: 10.1002/eji.201546119
|View full text |Cite
|
Sign up to set email alerts
|

T cells are necessary for ILC2 activation in house dust mite‐induced allergic airway inflammation in mice

Abstract: Allergic asthma is a chronic inflammation of the airways mediated by an adaptive type 2 immune response. Upon allergen exposure, group 2 innate lymphoid cells (ILC2s) can be rapidly activated and represent an early innate source of IL-5 and IL-13. Here, we used a house dust mite (HDM)-driven asthma mouse model to study the induction of ILC2s in allergic airway inflammation. In BALF, lungs, and lymph nodes, ILC2 activation is critically dependent on prior sensitization with HDM. Importantly, T cells are require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 50 publications
7
52
0
Order By: Relevance
“…critical to the development of a type-2 immune response (15)(16)(17)(18)(19)(20). Thus far, there has been little evidence implicating sPLA 2 -X as a regulator of these responses; however, a recent paper examining the effect of bee venom PLA 2 (bvPLA 2 ) in the periphery demonstrated that bvPLA 2 induces the release of IL-33, leading to the generation of ILC2s and subsequent antigen-specific T cell responses (21).…”
Section: Introductionmentioning
confidence: 99%
“…critical to the development of a type-2 immune response (15)(16)(17)(18)(19)(20). Thus far, there has been little evidence implicating sPLA 2 -X as a regulator of these responses; however, a recent paper examining the effect of bee venom PLA 2 (bvPLA 2 ) in the periphery demonstrated that bvPLA 2 induces the release of IL-33, leading to the generation of ILC2s and subsequent antigen-specific T cell responses (21).…”
Section: Introductionmentioning
confidence: 99%
“…1, from [39]) [29,34,40] or by surgically implanted means [23,24,27]. Studies investigating the mechanisms at the very start of allergic sensitization demonstrated that B-cells are dispensable for the primary CD4 + T-cell response, but crucial for expansion of primed Th2 cells and generation of central memory [28 ▪▪ ], ILC 2 were not an early source of Th2 cytokines, but contributed to allergic inflammation [26] together with IL-33 derived from monocytes [24], IL-23 secreted by bronchial epithelial cells [32], placenta growth factor [27] and lysophophatidylcholine [36]. Th2 and Th17 inflammatory pathways seemed to be reciprocally regulated in asthma [41].…”
Section: Introductionmentioning
confidence: 99%
“…BP SCIT treatment greatly reduced the number of BALF and lung ILC2s (Figure A, identified as Lin − [CD3 − CD19 − B220 − DX5 − FcɛRI − GR‐1 − CD11c − ],CD45 + , ST2 + , CD127 + , CD25 + in BALF and in lung). Li et al demonstrated that accumulation of ILC2s is dependent on the presence of Th2 cells. BP SCIT decreased the Th2 cytokine production in the lung draining lymph nodes (Figure A) and largely inhibited the accumulation of T cells to the bronchoalveolar compartment (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…BAL inflammatory cells were obtained by intratracheal cannulation, and the airway lumen was lavaged 3× with the same millilitre PBS containing 0.1 mmol/L EDTA. Cell differentiation was done by flow cytometric analysis as described before . BALF was stored at −20°C until IL‐5 was determined by ELISA (Ready set go!, eBioscience Inc via Immunosource, Halle‐Zoersel, Belgium).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation